PERCEPÇÃO DE TUTORES SOBRE A ALIMENTAÇÃO DE CÃES E GATOS NOS MUNICÍPIOS DE AQUIDAUANA E ANASTÁCIO-MS. - LONGO, Luise Fernanda da Rocha; MENDONÇA, Ana Paula Vargas; BARONI, Thais de Abreu Toledo; AIRROS, Eliane Corrêa; GARCIA, Elis Regina de Moraes (ANAIS DO ENIC, 2023)
-